IMPROVING TEACHERS’ ABILITY IN CLASS MANAGEMENT THROUGH DEMONSTRATION METHODS AT SLB PELITA HATI PEKANBARU - Yasni Yasni (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper is based on the low teacher's ability to manage classes at SLB Pelita Hati Pekanbaru. It is seen from 1) there are some teachers who cannot manage student seats properly, 2) there are a number of classrooms that do not have study schedules, class plans, and so on, and 3) there are some classes whose atmosphere is less orderly, which can be seen from the classes whose are not orderly and noisy during the learning process. Based on the formulation of the problem, the purpose of the research is, therefore, for knowing teachers’ ability in managing classes and to be improved through the demonstration method at SLB Pelita Hati Pekanbaru. The research uses the School Action Research design of the Kurt Lewin model. The main concept of PTS according to Kurt Lewin consists of four components, planning, action, observation, and reflection. Based on the description of data processing and discussion, it can be concluded that the teacher's ability in class management was obtained in the first cycle at 56% in the good category and in the second cycle it increased to 87% in the good category. It means that the application of the demonstration method for increasing teachers’ ability to manage classes at SLB Pelita Hati Pekanbaru works.